Vesicle size determines unitary exocytic properties and their sensitivity to sphingosine - Flašker, Ajda (2018)
Neuroendocrine cells contain small and large vesicles, but the functional significance of vesicle diameter is unclear. We studied unitary exocytic events of prolactin-containing vesicles in lactotrophs by monitoring discrete steps in membrane capacitance. In the presence of sphingosine, which recruits VAMP2 for SNARE complex formation, the frequency of transient and full fusion events increased. Vesicles with larger diameters proceeded to full fusion, but smaller vesicles remained entrapped in transient exocytosis. The diameter of vesicle dense cores released by full fusion exocytosis into the extracellular space was larger than the diameter of the remaining intracellular vesicles beneath the plasma membrane. Labeling with prolactin- and VAMP2-antibodies revealed a correlation between the diameters of colocalized prolactin- and VAMP2-positive structures. It is proposed that sphingosine-mediated facilitation of regulated exocytosis is not only related to the number of SNARE complexes per vesicle but also depends on the vesicle size, which may determine the transition between transient and full fusion exocytosis.